The Evaluation of Industrial Work Practices Program in Accounting Students at Vocational High School 50, Jakarta - F Septia Anggriawan (KnE Social Sciences, 2019)
Industrial Work Practice Program (Prakerin) is expected to be a means for students to become professional workers who are ready to find a way out of the problems faced in the future. However, the conditions and facts on the ground today are not as expected. This study aims to evaluate how the context, input, process, and results in the industrial work practice program in the Department of Accounting at Vocational High School 50 Jakarta. The type of research is evaluation research with CIPP evaluation model (Context, Input, Process, Product). The method used is quantitative methods. Quantitative data were collected through questionnaires distributed to 31 respondents. The results of the study conclude that the program of industrial work practices in the Department of Accounting at Vocational High School 50 Jakarta is in the good category, but still needs improvement in the input and process components.  Keywords: Industrial Work Practice Program, Evaluation, Vocational High School